2012
DOI: 10.1073/pnas.1119527109
|View full text |Cite
|
Sign up to set email alerts
|

Different glutamate receptors convey feedforward and recurrent processing in macaque V1

Abstract: Neurons in the primary visual cortex (V1) receive feedforward input from the thalamus, which shapes receptive-field properties. They additionally receive recurrent inputs via horizontal connections within V1 and feedback from higher visual areas that are thought to be important for conscious visual perception. Here, we investigated what roles different glutamate receptors play in conveying feedforward and recurrent inputs in macaque V1. As a measure of recurrent processing, we used figure-ground modulation (FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
179
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(202 citation statements)
references
References 48 publications
13
179
2
Order By: Relevance
“…First, we applied microstimulation in one area while recording the oscillations in the other area. Second, we locally infused blockers of AMPA and NMDA receptors thought to be differentially involved in feedforward and feedback processing (24,25). All our results converged onto a straightforward conclusion: γ-oscillations in the visual cortex travel in the feedforward direction, whereas α-oscillations index feedback effects.…”
supporting
confidence: 55%
“…First, we applied microstimulation in one area while recording the oscillations in the other area. Second, we locally infused blockers of AMPA and NMDA receptors thought to be differentially involved in feedforward and feedback processing (24,25). All our results converged onto a straightforward conclusion: γ-oscillations in the visual cortex travel in the feedforward direction, whereas α-oscillations index feedback effects.…”
supporting
confidence: 55%
“…Furthermore, contextual modulation requires the transmission of a great deal of information, and about 75% of all cortical connections are directly between pyramidal cells (Braitenberg and Schuz, 1991). Direct evidence of a role for NMDARs in contextual modulation was shown by Self et al (2012) using the well-established phenomenon of figure-ground modulation. This was almost abolished when NMDARs were blocked in V1, whereas the purely feedforward component of pyramidal cell response was largely unaffected.…”
Section: Modulation That Amplifies Responses To Rf Inputmentioning
confidence: 99%
“…In support of this argument, a recent study showed that figure-ground modulation is suppressed by local injection of an NMDA antagonist into V1. 51 Given that figure-ground modulation depends on top-down signals from higher-order visual areas, 26,27 the authors suggested this effect may be due to a blockade of NMDA spikes in the apical pyramidal dendrites of V1 neurons. This would explain Anesthetics can inhibit the hyperpolarization-activated current I h , a leak conductance, which uncouples the somatic and dendritic compartments of the pyramidal cell under physiological conditions.…”
Section: The Effects Of General Anesthetics On Apical Dendrites Of Pymentioning
confidence: 99%